MEKANISME OPERASIONALISASI SAHAM SYARI’AH DI INDONESIA DAN NEGARA LAIN - Jihad, Azka Amalia; Ramly, Ar Royyan (JURNAL EKONOMI DAN BISNIS ISLAM, 2016)
Islamic stocks is one of the instruments in islamic capital market which isoperated based on islamic principles. Islamic stocks are the securities proof ofequity participations in the company and with the evidence of these investments,the shareholders are entitled to receive part of the profits. Operationalmechanisms of islamic stocks is differently in each country. There are someproblems of the mechanisms on screening process. Assessment criteria of islamicstocks broadly divided into qualitative and quantitative criteria. Qualitativecriteria are based on halal and haram, while quantitative criteria are based onthe financial performance of the company. There is a differences of shari?acriteria in each country, specially at JII, DJIM, and KLSI. The differences willimpact to growth and development of islamic stocks in each country.